Penegakan Hukum Terhadap Tindak Pidana Penjualan Smartphone Ilegal Dalam Perspektif Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Kartadinata, Andriansyah (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2024)
The aim of writing this scientific work is of course to determine law enforcement regarding criminal acts of illegal smartphone sales in the perspective of Law Number 8 of 1999 concerning Consumer Protection with data collection techniques using normative juridical methods and library research. The research results show that the distribution of illegal smartphones can be overcome by implementing Article 62 Paragraph (1) in conjunction with Article 8 Paragraph (1) letter a of Law no. 8 of 1999 relating to consumer protection with the threat of a maximum prison sentence of five years and a maximum fine of 2 billion Rupiah as well as Article 52 Juncto Article 32 Paragraph (1) of Law no. 36 of 1999 concerning Telecommunications with the threat of a maximum prison sentence of 1 year or a maximum fine of one hundred million rupiah.